Effects of different types of verbal encouragement on ankle force and muscle activity - Taddei, Ulisses T.; Trombini-Souza, Francis; Ferreira, Jane S. S. P.; Matias, Alessandra B.; Inoue, Rafael S.; Ribeiro, Fernanda I. A.; Daré, João V. L.; Panighel, João P. A.; Calori, Renan; Santana, Pamela A.; Dalfolo, Milene E.; Sacco, Isabel C. N. (Brazilian journal of physical education and sport, 2018)
The aim of this study is to investigate (i) the effect of live and recorded verbal encouragement on muscle activity and ankle force; (ii) the effect of communication/extroversion on the variables; (iii) the reliability intra and inter examiners of the variables. Twenty healthy-youngers were assessed by surface electromyography of tibialis anterior and ankle flexion force by an ergometer twice, with one week apart. No difference was found between ankle force (p = 0.373) and root mean square values (RMS) (p = 0.207) for any of the conditions assessed on day 1 nor between examiners 1 and 2 for both live and recorded conditions in RMS (p = 0.207) and force (p = 0.373). Between the 1st and 7th days, there were no differences for any of the conditions on RMS (main effect “Day” p = 0.261, “condition” p = 0.568, interaction p = 0.936) or force (main effect“Day” p = 0.889, “condition” p = 0.781, interaction p = 0.961). Intraclass correlation coefficients (ICCs) for the ankle force were, for without verbal encouragement (ICC2, k = 0.880), live verbal encouragement of examiner 1 (ICC2, k = 0.870), and recorded verbal encouragement of examiner 1 (ICC2, k = 0.920). RMS without verbal encouragement condition (ICC2, k = 0.860), live verbal encouragement of examiner 1 (ICC2, k = 0.930) and recorded verbal encouragement of examiner 1 (ICC2, k = 0.920). Reproducibility between the two examiner’s live encouragements for ankle force (ICC3, k = 0.981) and RMS (ICC3, k = 0.920). There was no effect of the presence or type of the augmented feedback in RMS and ankle force. We conclude that verbal encouragement does not influence ankle torque or muscle activity and there is good to excellent intra and inter rater reliability for subjects’ performance regardless of verbal encouragement modality. In addition, we observed that psychological traits Communication and Emotional stability does not affect the subjects’ strength performance at the ankle.